Spontaneous Rupture of Renal Metastasis from Hepatocellular Carcinoma - Kinoshita, Osamu (Case Rep Surg, 2017)
We report a rare life-threatening case of spontaneous rupture of renal metastasis from hepatocellular carcinoma (HCC) that was managed by emergent transcatheter arterial embolization (TAE). A 76-year-old woman diagnosed with HCC presented with acute back pain in her right side and was transferred to our hospital. Initial enhanced computed tomography revealed retroperitoneal hemorrhage from the right kidney, which was retrospectively diagnosed as a spontaneous rupture of the metastatic renal tumor from the primary HCC. Detailed examination identified an active retroperitoneal hemorrhage from the lesion and the patient's condition became hemodynamically unstable; hence emergent TAE was performed. The hospitalization period after the TAE was uneventful and sorafenib was subsequently administered. Unfortunately, two months after the TAE, the tumor locally progressed within the retroperitoneal space. Tumors were controlled by repeated TAE as the patient did not want to undergo a nephrectomy. Consequently, she survived for more than one year after emergent TAE, exhibiting low levels of tumor marker. After rupture of the metastatic renal HCC, tumors were expected to progress into the retroperitoneal space, and nephrectomy was the next possible radical treatment to offer the best chance of long-term disease control.